GABA Concentrations in the Anterior Cingulate Cortex Are Associated with Fear Network Function and Fear Recovery in Humans - Levar, Nina; van Leeuwen, Judith M. C.; Puts, Nicolaas A. J.; Denys, Damiaan; van Wingen, Guido A. (Frontiers in Human Neuroscience, 2017)
Relapse of fear after successful treatment is a common phenomenon in patients with anxiety disorders. Animal research suggests that the inhibitory neurotransmitter γ-aminobutyric acid (GABA) plays a key role in the maintenance of extinguished fear. Here, we combined magnetic resonance spectroscopy and functional magnetic resonance imaging to investigate the role of GABA in fear recovery in 70 healthy male participants. We associated baseline GABA levels in the dorsal anterior cingulate cortex (dACC) to indices of fear recovery as defined by changes in skin conductance responses (SCRs), blood oxygen level dependent responses, and functional connectivity from fear extinction to fear retrieval. The results showed that high GABA levels were associated with increased SCRs, enhanced activation of the right amygdala, and reduced amygdala-ventromedial prefrontal cortex connectivity during fear recovery. Follow-up analyses exclusively for the extinction phase showed that high GABA levels were associated with reduced amygdala activation and enhanced amygdala-ventromedial prefrontal cortex connectivity, despite the absence of correlations between GABA and physiological responses. Follow-up analyses for the retrieval phase did not show any significant associations with GABA. Together, the association between GABA and increases in SCRs from extinction to retrieval, without associations during both phases separately, suggests that dACC GABA primarily inhibits the consolidation of fear extinction. In addition, the opposite effects of GABA on amygdala activity and connectivity during fear extinction compared to fear recovery suggest that dACC GABA may initially facilitate extinction learning.